PERSEPSI PERSONIL SALON KECANTIKAN TENTANG KOMPETENSI MAHASISWA DALAM PELAKSANAAN PENGALAMAN LAPANGAN INDUSTRI PROGRAM STUDI PENDIDIKAN TATA RIAS DAN KECANTIKAN JURUSAN KK FT-UNP - Marbun, Resida Damiana; Rahmiati, Rahmiati; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2015)
This research is motivated because of the presence of different perceptions expressed by personnel beauty salon in the city of Padang , seen from the indicators : Competence Affective and Psychomotor Competency . The purpose of this study was to obtain information about : ( 1 ) Perception Of Beauty Salon Personnel Competencies Affective Implement Field Experience In Industry ( PLI ) Education Prodi Makeup and Beauty Department KK FT - UNP . ( 2 ) Perception Of Beauty Salon Personnel Competence Psychomotor Implement Field Experience In Industry ( PLI ) Education Prodi Makeup and Beauty Department KK FT - UNP .This research is descriptive Quantitative which describe , explain or interpret the data as they are. The population in this study were the supervisors and employees working for about a year in a beauty salon , amounting to 40 people . The sample in this study is the entire population , which is taken by total sampling , the data used is primary data where data collection in this study conducted by questionnaire or questionnaire totaling 67 items . The data analysis technique used is the percentage of engineering and research data is processed memalalui SPSS version 16 and analyzed using descriptive statistics .The results showed that the attitude of competence scores ( Affective ) students in carrying Industrial Field Experience ( PLI ) including both categories of 83.1 % , and competence skills ( psychomotor ) students including both categories of 83.1 % . Of both indicators we can see that the perception of beauty salon personnel to student competence in the implementation of Industrial Field Experience ( PLI ) Education Program Makeup and Beauty Department KK FT - UNP was in both categories with a percentage of 83.1 % .